Quantum chemical approach for highly durable anion exchange groups in solid-state alkaline fuel cells. Issue 43 (12th April 2016) - Matsuyama, K.; Ohashi, H.; Miyanishi, S.; Ushiyama, H.; Yamaguchi, T.
Abstract : The durability of anion exchange groups against OH − ion that decomposed fast. Abstract : Durable anion exchange groups are required for solid-state alkaline fuel cells. In the present study, the lowest unoccupied molecular orbital (LUMO) was employed as a design guideline for durable anion exchange groups. The correlation between the LUMO and the durability of the anion exchange group was clarified.